Vascular protective effect and its possible mechanism of action on selected active phytocompounds: a review - Kamaruddin, Nur Aqilah; Abdullah, Muhammad Nazrul Hakim; Jun, Jie Tan; Lim, Vuanghao; Lai, Yen Fong; Abd Ghafar, Siti Aisyah; Yoke, Keong Yong (Hindawi Limited, 2022)
Vascular endothelial dysfunction is characterized by an imbalance of vasodilation and vasoconstriction, deficiency of nitric oxide (NO) bioavailability and elevated reactive oxygen species (ROS), and proinflammatory factors. ,is dysfunction is a key to the early pathological development of major cardiovascular diseases including hypertension, atherosclerosis, and diabetes. ,erefore, modulation of the vascular endothelium is considered an important therapeutic strategy to maintain the health of the cardiovascular system. Epidemiological studies have shown that regular consumption of medicinal plants, fruits, and vegetables promotes vascular health, lowering the risk of cardiovascular diseases. ,is is mainly attributed to the phytochemical compounds contained in these resources. Various databases, including Google Scholar, MEDLINE, PubMed, and the Directory of Open Access Journals, were searched to identify studies demonstrating the vascular protective effects of phytochemical compounds. ,e literature had revealed abundant data on phytochemical compounds protecting and improving the vascular system. Of the numerous compounds reported, curcumin, resveratrol, cyanidin-3-glucoside, berberine, epigallocatechin-3-gallate, and quercetin are discussed in this review to provide recent information on their vascular protective mechanisms in vivo and in vitro. Phytochemical compounds are promising therapeutic agents for vascular dysfunction due to their antioxidative mechanisms. However, future human studies will be necessary to confirm the clinical effects of these vascular protective mechanisms.